Role of Monocyte Lymphocyte Ratio as a Predictor of Mortality in Patients with Acute Respiratory Distress Syndrome - Yeasmin, Farah; Ahsan, A S M Areef; Fatema, Kaniz (Bangladesh Critical Care Journal, 2025)
Background: Early outcome prediction in Acute Respiratory Distress Syndrome is vital for better management. Existing tools like scores, imaging, and biomarkers have limitations, while Monocyte Lymphocyte Ratio offers a simpler, efficient alternative for predicting mortality more accurately. Aims: To evaluate the association between monocyte lymphocyte ratio with mortality in patients with Acute Respiratory Distress Syndrome. Methods: This cohort study was carried out in the Department of Critical Care Medicine, BIRDEM General Hospital, Dhaka, for 18-months following ethical approval. A total of 95 diagnosed ARDS cases were included who fulfilled the enrollment criteria. Along with clinical assessment sample for CBC was sent within 24 hours of diagnosis and documented the monocyte and lymphocyte counts. Patients were observed up to 28 days for mortality. Data were collected in separate record forms and analyzed by SPSS 22. Results: The mean Monocyte Lymphocyte Ratio (MLR) was significantly higher in non-survivors (0.59±0.46) than survivors (0.37±0.12) (p<0.05). MLR differed significantly in patients with respiratory distress, hypotension, and fatigue. It increased with ARDS severity: severe (0.56±0.49), moderate (0.30±0.12), and mild (0.25±0.14), though intergroup difference wasn’t significant (p>0.05). Only 35% survived at 28 days. A significant negative correlation existed between MLR and PaO2/FiO2 (r = -0.314, p = 0.002). ROC analysis showed MLR had better predictive accuracy (AUC = 0.69, cut-off 0.26) than NLR (AUC = 0.56, cut-off 10.0) for ARDS mortality. Conclusion: Monocyte Lymphocyte Ratio can predict ARDS mortality and, being affordable and simple, is a practical tool for resource-limited settings like ours. Bangladesh Crit Care J September 2025; 13 (2): 91-99